INSTANCES OF THE VOLITIONAL SCHEMA [(EU) QUERO LÁ VINF] IN CONTEMPORARY PORTUGUESE (PERcursos Linguísticos, 2022)
In this article, we chose as an object of research the volitional scheme [(eu) quero [lá Vinf]] and its instantiation in contemporary Portuguese, as presented in AUTHOR (2022). Based on Functionalism, from Traugott and Trousdale (2013), Hilpert (2014) and Bybee (2010; 2015), among others, we raised and analyzed instantiations of the referred scheme and found that it is divided into two sub-schemes: one of positive polarity, encoded as [[(eu) quero] [lá Vinf]], and another of negative polarity - [[(eu) quero lá] [Vinf]]. Based on qualitative and quantitative analysis, according to Cunha Lacerda (2016), we found that such sub-schemes present other distinctions, in addition to polarity, such as level of compositionality, productivity and intersubjectivity.